Profile context management in ubiquitous computing. (27th November 2012) - Baloch, Raheel Ali; Crespi, Noel
By utilising various types of contextual data acquired from users' devices, enhanced context–aware services and applications can be developed and deployed. But current context management systems are based on a server–client approach, which hinders their widespread adoption in an ad–hoc environment. In addition, performance issues introduced because of context dependency in a ubiquitous environment still need to be addressed. This paper presents the idea of profile context to address the problem of context dependency, and also proposes an open framework for context acquisition, management and distribution in a ubiquitous environment. Bringing together context information and context updates from various sources, support for context–aware decisions can be implemented efficiently in a mobile environment by addressing the issues related to context dependency using profile context.